(untitled) (Research, Society and Development, 2020)
Cruise tourism is one of the fastest growing segments of the last 20 years. Its worldwide importance nowadays reflects in the impacts that the sector generates in the local economies. In this context, this work aims to analyze the scientific studies published between the period of 1990 to 2019, using the SCOPUS database. A total of 82 related works were found, which, after being verified, were reduced to 38 articles. Of these, 17 presented relevance for the present study. From the analysis of these articles it was concluded that a great part of the researches is related to the pattern of expenses incurred by tourists in the destinations. The other portion relates to the overall economic impact generated by the maritime cruises. Some reflections on possible research gaps are inserted at the end of this work.